PATRIARCHAL SOCIETY IN TAR BABY BY TONI MORRISON - Kamalakkannan, K. M.; Jothimani, M. (International Journal of Psychosocial Rehabilitation, 2020)
Everybody wants to have its own identity in the society. People live in the society with the identity acquired from the family’s orancestor’s name. Earlier it was believed that women can only take care of their family and home and their work was to cook foodin the kitchen for the family and children. Professionally, it was not important for a woman to have her own identity. A womanwas only known in the society as one’s sister, daughter, or a mother and for centuries, the world was dominated by patriarchalsocieties. In the patriarchal dominated society, men used to believe that only men can work and earn bread and butter for thefamily and women’s prime contribution to the family was to set up the kitchen and make arrangements for food for three times.This thought was acquired and run in the families from their previous generations. This male domination was also made powerfulby the religious and cultural norms. Conservative cultures can also be blamed for this maligned thought and giving one genderpriority over the other. The patriarchal dominated society and gender discrimination was also prevailed in the developed countriesequally as was in the underdeveloped nations